Does Therapeutic Dose of Sildenafil Citrate Treatment Lead to Central Serous Chorioretinopathy in Patients With Erectile Dysfunction?. (September 2013) - Damar, Elif; Toklu, Yasin; Tuncel, Altug; Balci, Melih; Aslan, Yilmaz; Simsek, Saban; Atan, Ali
The possible effects of sildenafil citrate administration at therapeutic dosage on visual acuity, color vision, intraocular pressure, macular thickness, macular volume, and central serous chorioretinopathy in patients with erectile dysfunction were evaluated. The study consisted of 43 male patients diagnosed as having erectile dysfunction according to the first five question version of International Index of Erectile Function (IIEF-5). All patients were given sildenafil citrate 50 mg po 2 to 3 times/week for a month. The patients were evaluated at the first week and at the end of the treatment. The macular thickness and volume assessments with optic coherence tomography did not differ significantly in foveal, parafoveal areas, parafoveal superior hemisphere, parafoveal inferior hemisphere, parafoveal temporal, superior, nasal, and inferior quadrants. Central serous chorioretinopathy was not found in any of the patients.